ANALISA PENGARUH INTERNAL MARKETING, BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA PADA PT. TRANS BERJAYA KHATULISTIWA - Alessandro Del Piero Riwu; Joan Yuliana Hutapea; Francis M. Hutabarat (POLITEKNIK LP3I JAKARTA, 2024)
This research aims to determine the influence of Internal Marketing and Organizational Culture on the level of Job Satisfaction at PT. Trans Berjaya Khatulistiwa. The research method used was quantitative, with sampling carried out using non-probability sampling techniques and involving 54 respondents who filled out questionnaires. The research results show that both Internal Marketing and Organizational Culture have a partially positive and significant influence on Job Satisfaction. Overall, these two variables also have a positive and significant influence simultaneously on Job Satisfaction. The coefficient of determination value reached 67.3%. This shows that 67.3% of decisions are influenced by Internal Marketing and Organizational Culture while the remaining 32.7% is influenced by other unknown variables. Key words: Internal Marketing, Organizational Culture, Job Satisfaction